Stress, anxiety, depression and social media in generation Z: A scoping review - Harefa, Juli Tri Vemina; Manik, Kesya Anggita; Habehan, Zefanya Liliana; Juniarta; Cicilia, Sarah Lidya (JOURNAL OF Mental Health Concerns, 2025)
Background: Social media is deeply embedded in Generation Z’s daily routines, shaping their social lives and psychological well-being. Growing concerns have emerged regarding its adverse effects on stress, anxiety, and depression. Purpose: This study was conducted to review and map existing research that explores the link between social media use and mental health outcomes in this population. Method: A scoping review conducted through a systematic search of three databases: PubMed, Science Direct, and Medline. The selection criteria focused on studies published in English or Indonesian between 2015 and 2025. This study concentrated on research examining the correlation between social media usage and mental health outcomes, particularly stress, anxiety, and depression, in Generation Z. Results: Fourteen eligible articles were analyzed. Three main themes were identified: (1) Type of user, encompassing excessive and addictive users, (2) Psychological symptoms, characterized by diminished social functioning, memory impairment, feelings of loneliness, and sleep disruptions, and (3) Mental Health issues, including stress, anxiety, and depression. Conclusion: Evidence indicates a correlation between social media usage and negative mental health issues in Generation Z. Preventive strategies and targeted interventions are essential to address and mitigate stress, anxiety, and depression among social media users. Keywords: Anxiety; Depression; Generation Z; Social Media; Stress.